Sensitivity characterization of cladding modes in long-period gratings photonic crystal fiber for structural health monitoring. (August 2015) - Zheng, Shijie; Shan, Baohua; Ghandehari, Masoud; Ou, Jinping
Highlights: The sensitivity of PCF-LPG as function of external conditions was examined. PCF can produce numerous modes, including cladding modes with ultra-sensitive coupling. The maximum or minimum sensitivity for the PCF is determined by cladding mode dispersion. Two parameter sensing can be achieved with PCF-LPG. Abstract: Sensitivity of fiber cladding modes coupled with long-period gratings (LPGs) in photonic crystal fiber (PCF) are investigated with respect to external conditions such as temperature, strain, the surrounding refractive index, curvature, and torsion. What we have found is that the application of MODE Solutions to a given PCF structure can produce a large amount of modes, where the dispersion and group velocities are generally a function of wavelength, hence the cladding modes with ultra-sensitive spectrum behavior for LPG coupling and sensing purpose. By means of analyzing equation of phase-matching condition, we can better understand sensitivity characteristics of cladding modes. The results of numerical computation indicate that the maximum or minimum sensitivity of a cladding mode coupled with PCF-LPG is predetermined by its dispersion, which is also influenced by the PCF structure geometry. The design of the structural geometry gives a large degree of freedom with respect to tailoring its optical properties. Multi-parameter sensing is discussed in light of utilizing the resonances at discrete wavelength locations distinguishing and simultaneously measuring two parameters in a PCF-LPG.